Fishes species diversity and seasonal variation in the lower basin of Nanay River, Peru - Correa, Ericka (2010)
This paper reports on the diversity of fish in the lower basin of the Nanay River, a tributary of the Amazon River. This area is subjected to indiscriminate harvesting of fish for ornamental purposes and for direct consumption. Using trawl nets (10 x 2.5 m, 5 mm mesh), we fished in the dry season (August and September 2007) and wet season (February 2008) in three places in the Nanay River. 1626 individuals were collected, corresponding to 86 species of 23 families and five orders. The number of species varied between 13 and 21 in the dry season and between 18 and 26 species during the growing season. Characiformes, Siluriformes and Perciformes were the dominant orders. 76% of individuals had small sizes. 65% of the recorded species have ornamental use.